2022
DOI: 10.1021/acsestwater.1c00493
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Intrusion on Disinfection Byproduct Formation in Intermittent Distribution Systems

Abstract: Intermittently operated distribution systems serve over one billion people and may be impacted by the intrusion of contaminated waters carrying disinfection byproduct (DBP) precursors. The impact of intrusion on the formation of 19 DBPs was evaluated in an intermittent water system supplied by deep aquifers in Dhaka, Bangladesh. Untreated piped water samples were collected from residential taps and chlorinated under controlled conditions. Chloride, dissolved organic carbon, and the artificial sweetener sucralo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(14 citation statements)
references
References 39 publications
(69 reference statements)
0
14
0
Order By: Relevance
“…Although high concentrations were found in groundwater across samples in both cities (12–1400 μg/L), I-THM concentrations were low in most samples. On the contrary, Furst et al found low (<12 μg/L) bromide concentrations in most water samples tested from Dhaka, Bangladesh. While higher concentrations of Br-DBPs found in the study conducted in India were due to higher concentrations of bromide in source water, the second study that investigated the effect of intrusion did not find significant effects on bromide or Br-DBP concentrations.…”
Section: Factors That Influence Dbps In Iwsmentioning
confidence: 92%
See 4 more Smart Citations
“…Although high concentrations were found in groundwater across samples in both cities (12–1400 μg/L), I-THM concentrations were low in most samples. On the contrary, Furst et al found low (<12 μg/L) bromide concentrations in most water samples tested from Dhaka, Bangladesh. While higher concentrations of Br-DBPs found in the study conducted in India were due to higher concentrations of bromide in source water, the second study that investigated the effect of intrusion did not find significant effects on bromide or Br-DBP concentrations.…”
Section: Factors That Influence Dbps In Iwsmentioning
confidence: 92%
“…Furst et al are the only publications, to the best of our knowledge, reporting measurements of bromide and iodide concentrations and Brand I-DBPs in IWS systems. 32,33 Furst et al 32 found higher bromide concentrations in groundwater in two cities with IWS, Jaipur and Jodhpur, India, and also higher bromide concentrations between the surface water source of Jaipur (140 μg/L) compared to Jodhpur (10 μg/L), which led to higher concentrations of brominated haloacetonitriles that contributed the majority of the toxic potency-weighted DBP concentrations and higher bromine substitution factors. Although high concentrations were found in groundwater across samples in both cities (12−1400 μg/L), I-THM concentrations were low in most samples.…”
Section: Stagnationmentioning
confidence: 99%
See 3 more Smart Citations